2021
DOI: 10.3389/fcell.2021.670021
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte Meiotic Competence in the Domestic Cat Model: Novel Roles for Nuclear Proteins BRD2 and NPM1

Abstract: To participate in fertilization and embryo development, oocytes stored within the mammalian female ovary must resume meiosis as they are arrested in meiotic prophase I. This ability to resume meiosis, known as meiotic competence, requires the tight regulation of cellular metabolism and chromatin configuration. Previously, we identified nuclear proteins associated with the transition from the pre-antral to the antral follicular stage, the time at which oocytes gain meiotic competence. In this study, the objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…2 A, 3 , and 5 ). ASRGL1 is an enzyme that catalyzes the hydrolysis of l -asparagine that was previously found to be expressed during oocyte development 41 and in the sperm tail of rats and humans. Hashemitabar et al 42 also found that ASRGL1 was highly expressed in cases of asthenozoospermia.…”
Section: Discussionmentioning
confidence: 99%
“…2 A, 3 , and 5 ). ASRGL1 is an enzyme that catalyzes the hydrolysis of l -asparagine that was previously found to be expressed during oocyte development 41 and in the sperm tail of rats and humans. Hashemitabar et al 42 also found that ASRGL1 was highly expressed in cases of asthenozoospermia.…”
Section: Discussionmentioning
confidence: 99%
“…After 26 h incubation, LGALS3BP protein inhibition was achieved by transfecting anti-LGALS3BP antibodies into COCs as previously described [ 57 , 58 ], using the Chariot peptide nanoparticle transfection reagent (Active motif, Carlsbad, CA, USA). Antibody-Chariot complexes were made according to manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that BRD may have a context-dependent function in cellular homeostasis. Moreover, BRD-containing proteins can regulate downstream gene expression, which makes them valuable targets for the study of fertility, neurological and immunological diseases, and cancer therapy [ 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%